The Known Unknowns of the Human Dendritic Cell Network - Durand, Mélanie; Segura, Elodie (Frontiers in Immunology, 2015)
Dendritic cells (DC) initiate and orient immune responses and comprise several subsets that display distinct phenotypes and properties. Most of our knowledge of DC subsets biology is based on mouse studies. In the past few years, the alignment of the human DC network with the mouse DC network has been the focus of much attention. Although comparative phenotypic and transcriptomic analysis have shown a high level of homology between mouse and human DC subsets, significant differences in phenotype and function have also been evidenced. Here we review recent advances in our understanding of the human DC network and discuss some remaining gaps and future challenges of the human DC field.